The legal regime of foreign private investment in Sudan and Saudi Arabia - El Sheikh, Fath el Rahman Abdalla (Cambridge University Press, 2003)
Although developing countries require foreign investment for growth, investors often encounter a range of obstacles in the existing economic order. This comparative study of two developing countries with similar socio-ethnic backgrounds--the Sudan and Saudi Arabia--considers how international and Islamic law have evolved in new directions in post-Soviet years. Topics include incentives and facilities for foreign investors, investment treaties, investment insurance programs and remedies for aggrieved investors